A high-performance guidance filter scheme with exact dynamic modeling of a pitch-yaw gimballed seeker mechanism. (October 2020) - Ahi, Behzad; Haeri, Mohammad
Highlights: Existing guidance filter schemes are reviewed and their weaknesses are highlighted. A novel guidance filter design is proposed. Computing Cramer-Rao bound, effects of various error sources are investigated. An exact guidance law based on compensating roll coupling terms is developed. Abstract: This paper is concerned with the problem of guidance filter design for a homing air defense missile using measurements of an on-board pitch-yaw gimballed seeker mechanism. This problem possess a highly nonlinear dynamic which is influenced by various error sources such as seeker's stabilization loop torque disturbances originated from pursuer's accelerations and angular velocities, significant channel couplings, time-delayed and noisy measurements of optical sensor besides the unknown target maneuvers. To handle the inherent nonlinearity of problem a wide variety of assumptions are made in literature to derive simplified engagement kinematics. In present work, performance degradations which might occur due to these simplifications are highlighted with the aid of deriving a general dynamic formulation for a pitch-yaw gimbal assembly. Then, a novel filter dynamic is suggested which requires no simplifying assumption in contrast with all existing solutions. Taking the advantages of proposed filter design, some beneficial points on generating accurate proportional navigation guidance commands are also presented. Comparative simulation analyses demonstrate the effectiveness of novel exact filtering scheme in comparison with the prominent existing solutions respecting the Cramer-Rao bound of estimation problem. The results of study, are generally applicable for performance enhancement in track loop control design of high accurate pointing systems.